Tuberculosis of the prostate presenting as benign prostatic hyperplasia. - Fazarina M; Tan, GH; Badrulhisham B; Shiran, MS; Tan, GC (Penerbit UKM, 2013)
Genitourinary system is the second most common site of tuberculosis (TB) after pulmonary system. Tuberculosis of the prostate is a rare manifestation of genitourinary tuberculosis. It is even more uncommon if occurring in an immune-competent individual. Prostate TB is usually an incidental finding in transurethral resection of prostate (TURP). Here, we report a case of TB of the prostate in a 70-year-old man who had benign prostatic hyperplasia for two years. TB was diagnosed incidentally post-TURP. In this report, we also discuss additional tests which may help in establishing the diagnosis of genitourinary tuberculosis.